The secret dreamworld of a shopaholic - Kinsella, Sophie (London, England : Black Swan, 2000)
"Meet Rebecca Bloomwood. She's a journalist. She spends her working life telling others how to manage their money. She spends her leisure time, shopping." "Retail therapy is the answer to all her problems. She knows she should stop, but she can't. She tries cutting back, she tries making More Money. But neither seems to work. The stories she concocts become more and more fantastic as she tries to untangle her increasingly dire financial difficulties. Her only comfort is to buy herself something - just a little something." "Can Becky ever escape from this dream world, find true love, and regain the use of her Switch card?"
Keywords: Finance, Personal -- Fiction; Shopping -- Fiction; Women journalists -- Fiction